Effect of stirring on solid solution hardening. (2021) - Adigun, O.D.; Oni, A.; Obadele, B.A.; Olusunle, S.O.; Abegunde, I.E.; Omonubi, K.B.
Abstract: In the present study, the influence of stirring speed on the solid solution hardening of cast aluminium alloy leading to improvement in microhardness values have been reported. Stir casting method was used to prepare percentage compositions of Al-Cu alloys between 0 and 15 wt% Cu. Different stirring speed of 0 rev/min, 10 rev/min, 50 rev/min and 90 rev/min were used to make test sample and materials produced were characterized for hardness. Hardness values of the 0–15 wt% Cu solute addition were observed to independently increase progressively with increase in stirring speed. The increase in microhardness observed is attributed to increase in the dispersion of Cu solute in the Al solution caused by the stirring action which contributed to impeding plastic deformation in the Al lattice. The study further indicates that stirring could be a vital metallurgical processing tool to enhance hardness during alloying.